The Impact of Beach Resorts to Community: Basis for a Community Awareness Program - Gonzales, Maria Luisa N. (European Journal of Applied Sciences, 2021)
Coastal areas are those which are most visited by tourists and many coastal area tourism presents the most important economic activity. Resorts tend to change the complexion of a community as outsiders in search of work, gravitate to them in droves. Mushrooming population growth can be observed in any of the popular resort areas found in the islands. Some beaches have man-made infrastructure, such as lifeguard posts, changing rooms, and showers. They may also have hospitality venues (such as resorts, camps, hotels, and restaurants) nearby. This study aimed to determine the impact of Beach Resorts to Community Development along social, environmental, and economic impact, its challenges encountered, in order to design a Community Awareness Program. It will be significant to the DOT, LGU, Tourism office, Local Residents, Resort owner and future researchers. It used the descriptive method of research by employing questionnaire and interview of the 7 beach resort owners, and 70 residents living around the beach resorts with 77 respondents. It used the frequency distribution, frequency count and weighted mean. Findings revealed that respondents were much benefitted in social, while benefited on economic and environmental impacts. However, with the different benefits derived by the beach resorts owner and residents there were encountered problems considered and was interpreted as serious. Thus, this study will provide an understanding of the impact affecting the sustainability of the beach resorts as a tourist destination hub that will lead to the development of the resorts and the community by formulating a community awareness program.